Applications of ATM in global networks. - Luetchford, J.C (IEEE Communications magazine)
This article describes the market drivers, objectives, and consequences of introducing ATM into public and private networks. To serve the diverse needs of environments and applications, ATM presents a broad choice of characteristics to users and providers. To harness this diversity and bring structure to the choices, this article discusses ATM transfer capabilities (ATCs) and quality of service (QoS) classes as specified in ITU-T Study Group 13. Industry aims to achieve consistency between the ITU-T and ATM Forum specifications. This article includes consideration of AALs and interworking in developing network strategies. Providers will offer a selection of the possible services defined for ATM. Also, each provider will communicate their strategy for preferred network utilization and efficient traffic through incentives to users